2014
DOI: 10.1007/s10995-014-1622-9
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Maternal Employment: Results from Three National Nutritional Surveys in Mexico

Abstract: To evaluate the association between maternal employment and breastfeeding (both duration and status) in Mexican mothers using data from three National Health and Nutrition Surveys conducted in 1999, 2006 and 2012. We analyzed data from the 1999 National Nutrition Survey, the 2006 National Nutrition and Health Survey, and the 2012 National Nutrition and Health Survey (NNS-1999, NHNS-2006 and NHNS-2012) on 5,385 mothers aged 12-49 years, with infants under 1 year. Multivariate logistic regression models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
4
15
1
1
Order By: Relevance
“…In this study, mothers engaged in full-time employment were more likely to cease breastfeeding. Numerous studies have shown a negative association of maternal postnatal employment on breastfeeding duration [ 13 , 30 , 40 , 42 , 43 , 44 ]. The key barriers for employed mothers to continue breastfeeding include privacy issues, low support from their workplace, fatigue, lack of break time to express milk, inflexible work schedules, and inadequate facilities for pumping and storing milk [ 40 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mothers engaged in full-time employment were more likely to cease breastfeeding. Numerous studies have shown a negative association of maternal postnatal employment on breastfeeding duration [ 13 , 30 , 40 , 42 , 43 , 44 ]. The key barriers for employed mothers to continue breastfeeding include privacy issues, low support from their workplace, fatigue, lack of break time to express milk, inflexible work schedules, and inadequate facilities for pumping and storing milk [ 40 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, full-time employed mothers were 27% less likely to breastfeed compared to non-employed mothers. 5 The level of support for breastfeeding working mothers receive at the workplace has been found to considerably influence their decision to continue with breastfeeding when they return to work, in addition to maternal characteristics such as educational attainment, their knowledge of breastfeeding, commitment, and other personal factors that influence their decision on breastfeeding. In a study among working mothers in Hong Kong, 6 whereas 85% of the full-time working mothers returned to work within 10 weeks following delivery, only 32% of the women were able to continue breastfeeding along with the work, and short working hours, and higher maternal education were found to be associated with exclusive breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…12 We found that 87.5% of the working women were breast feeding the babies for more than 6 months which is more than (61.5%) of the housewives, which shows a positive impact of employment on breast feeding, however a study by Pasquel et al says that formally employed mothers were 20% less likely to breastfeed compared to non-formally employed mothers and 27% less likely to breastfeed compared to unemployed mothers. 13 Generally maternal employment is thought to be well contributing to maternal psychosocial well-being through the provision of social support and resources from the workplace, and hence it is deducted that employed mothers would be more positive parents. 14…”
Section: Discussionmentioning
confidence: 99%